Avaliação do potencial antioxidante do extrato bruto da entrecasca do caule da sucupira branca (Pterodon pubescens) por ressonância paramagnética eletrônica - Teixeira, Kátia de Souza Chagas (2016)
In the Brazilian Cerrado, there is a great diversity of vegetal species of which locals commonly collect materials to be used against many diseases. There are some studies about their antioxidant properties that might be related to the healing processes. In this work we evaluate the antioxidant potential of the extract crude of Pterodon pubescens, a typical Brazilian plant found in the Cerrado. The locals know this specie as Sucupira Branca, a medicinal plant. We used the X-band Electron Paramagnetic Resonance (EPR) at room temperature to evaluate its antioxidant activity. The measurements were performed in different concentrations of the extract diluted in the free radical DPPH (2, 2-diphenyl-1-picrylhydrazyl) solution at 1mM. The analyses were taken to obtain the material capability to neutralize the action of the radical. We observed a clear relation between the signal decay and the extract concentration. The percentage of DPPH action inhibition was also determined. We verified that small amount of extract is enough to efficiently reduce the DPPH radical, indicating that the crude extract of Pterodon pubescens has a great antioxidant property.